A construção de uma identidade viável na pesquisa LGBT - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
In this dissertation, concerned with issues of gender and sexualities in the field of language studies, I reflect on the construction of a viable identity in LGBT research, continuing my own academic and personal journey, now shared with the collectivity: the LGBT community in its infinite expressions and bodies. This paper’s main objective is to reflect the concrete action of academic research in languages in the lives of LGBT people, presenting the LGBT community perspectives towards the university. The hypothesis raised, proven by this endeavor, is that academic research in language, gender, and sexualities – no matter how much it proposes to do so – fails to effectively reach the lives it cares about. Guiding me in Performativity Theory, within the New Pragmatics framework, are Austin (1990); Butler (1997; 2003; 2004; 2021); Rajagopalan (2004; 2010) and Pinto (2013; 2015). To follow this theoretical and methodological path, I articulated the literature review, conducted in Digital National Library of Dissertations and Theses, resulting in eight master's degree papers; with the dialogue with twelve people identified by the dissidence of gender and sexualities, which through questionnaire, handwritten production and transcribed interview, according to their specific demands, narrated themselves, expressing how they understand themselves, how they understand gender and sexualities; how it is to occupy their own identity position in the world, the possible social limits they encounter, their relationship with the university space, and how they visualize and feel the research in the field of language studies and about themselves. The procedures’ approval is registered under the ethics committee process number 5.684.681. From this corpus, with the Textual Discourse Analysis (MORAES; GAGLIAZI, 2014), I, as a teacher and LGBT researcher, and the people who have been and written with me, developed the following categories for discussion: identity in performances; the body as a stage of performances; same university, different spaces and postures; violence; and acceptance. What presented itself as a primary consideration originated among provocations, attempts, comings and goings of this work writing process reaches people who research language, when I say that the questioning about the place we occupy and our bodies should be constant; and that the recognition of people identified by the dissidence of gender and sexualities, worrying about them, their life, their affections, the possibilities and potentials, beyond their contribution to research, cannot be absent, as is seen contemporarily and as I have demonstrated, by attributing to them the place of research subjects. Furthermore, I see that institutions, especially universities, have a long way to go in expanding access and guaranteeing the permanence of these bodies, which today find themselves condemned to the margins by violating the normativity of gender and sexualities. With this in mind, I propose actions to combat LGBTphobia and its violence, to be adopted in the context where I produce, research, teach, learn and live.
Keywords: Linguagem; Gênero; Sexualidade; Nova Pragmática; Teoria da Performatividade; Language; Gender; Sexuality; New Pragmatics; Performativity Theory; CNPQ::LINGUISTICA, LETRAS E ARTES